Investment Incentives and Effective Tax Rates in the Philippines : A Comparison With Neighboring Countries - Klemm, Alexander; Baqir, Reza.; Botman, Dennis (Washington, D.C. : International Monetary Fund, 2008)
We compare the general tax provisions and investment incentives in the Philippines to six other east-Asian economies-Malaysia, Indonesia, Lao, Vietnam, Cambodia, and Thailand. We calculate effective tax rates and find that general effective tax rates are relatively high in the Philippines, while investment incentives are comparable to those in neighboring countries. Tax holidays are most attractive for very profitable firms, creating redundancy, and for investment in short-lived assets. We also consider recently-proposed tax reforms that would replace tax holidays by a reduced corporate income tax rate or a low tax on gross receipts. The results suggest that this would result in stronger incentives to invest, while government revenue increases. Alternatively, replacing holidays with a general reduction in the corporate tax rate and offering accelerated depreciation will either not provide the same incentives or be very costly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet